2015
DOI: 10.1597/12-232
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Tooth Movement into New Bone Area Regenerated by Use of Bone Marrow–Derived Mesenchymal Stem Cells

Abstract: It is suggested that mesenchymal/carbonated hydroxyapatite transplantation therapy has great potential as a new treatment modality for bone regeneration in patients with cleft palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…We developed an alveolar bone regeneration method in patients with CL/P using human bone marrow mesenchymal stem cells (hBMSCs). The transplantation of hBMSC regenerated bone in a canine alveolar cleft model and orthodontic tooth movement was achieved in the regenerated bone (Sumi et al, ; Tanimoto et al, ; Yoshioka et al, ). However, puncture of the iliac bone is still necessary for bone marrow aspiration.…”
Section: Introductionmentioning
confidence: 99%
“…We developed an alveolar bone regeneration method in patients with CL/P using human bone marrow mesenchymal stem cells (hBMSCs). The transplantation of hBMSC regenerated bone in a canine alveolar cleft model and orthodontic tooth movement was achieved in the regenerated bone (Sumi et al, ; Tanimoto et al, ; Yoshioka et al, ). However, puncture of the iliac bone is still necessary for bone marrow aspiration.…”
Section: Introductionmentioning
confidence: 99%
“…MSC in combination with biomaterials, carry a great potential that has already been proven in animal studies and on first human cases. [17][18][19][20][21][22][23][24][25][26][27][28] Several aspects have to be taken into consideration when planning stem cell-enhanced bone regeneration.…”
Section: Stem Cellsmentioning
confidence: 99%
“…One of its major advantages is that maxilla-derived stem cells proliferation potential is probably unaffected by donor age, and only population doubling time seems to increase with donor age. 56 BM-MSC have already been used in the alveolar cleft regeneration on animal models [17][18][19][20][21][22] and in first clinical cases. 23-28 BM-MSC were by many investigators found suitable for craniofacial tissue engineering including calvarial bone defects 57-61 and both maxillary 62 and mandibular 63-67 bone reconstruction.…”
Section: Bone Marrow-derived Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we cultured and transplanted MSCs and carbonated hydroxyapatite particles into a bone defect area and observed that early bone regeneration occurred in the presence of transplanted MSCs [5]. Another study showed that when a tooth was moved to a site of bone that had been regenerated by MSCs and carbonated hydroxyapatite particle transplantation, the movement was the same as in normal bone [6]. Thus, normal bone remodeling appears to occur in regenerated bone.…”
Section: Introductionmentioning
confidence: 98%